Mathematics teachers' understanding of alternative assessment as applied in junior secondary schools in Gaborone (Botswana) - Raboijane, Botoka (My University, 2006)
An attempt to improve the quality of education in Botswana included an emphasis on alternative forms of assessment. This attempt however, has produced inconclusive results and the censure has often been on technical issues such as; lack of resources and overlooking the teachers’ understanding of the proposed innovation. A naturalistic research approach was undertaken by this study to investigate whether or not teachers at junior secondary schools in Botswana were using formative assessment when teaching mathematics as advocated in the RNPE. By employing the notion of currere, the study subjected three purposively sampled mathematics teachers drawn from three purposively sampled public junior secondary schools to an autobiographical process to reflect on their practices. The research methods comprised classroom observations and interviews. In the light of Bernstein’s theory of pedagogic device, data was analyzed and interpreted. The findings of this study indicated that mathematics teachers’ assessment strategies are still traditional. Their practices are influenced by many factors more especially by the need to make sure that students do well in the public examinations. Their understanding of these factors determines their receptivity to the proposed change. These teachers need to put themselves on the spot, and question their taken-for-granted aspects of their work. Only this way, would they become aware of alternative cause of action they need to take and can regard themselves as “critical public intellectuals.”
Student Number: 0306365F Masters in Education School of Education
Keywords: Alternative assessment; Currere; Discourse; Pedagogic device; Recontextualization; Power relations; Social control